1993
DOI: 10.1159/000211136
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of the Stratum corneum Barrier Function in Blacks, Caucasians and Asians with Two Noninvasive Methods

Abstract: This study compared in man the in vivo barrier function of stratum corneum in three racial groups: black, Caucasian and Asian, by two noninvasive technics. They were transepidermal water loss (TEWL) determination measured with an evaporimeter and laser Doppler velocimetry (LDV) to measure the lag time before the vasodilatation induced by application of methyl nicotinate (10 μl of 0.5% solution in ethanol/propylene glycol 95/5 v/v). Both methods were performed simultaneously on each forearm of 7 black, 8 Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 11 publications
2
67
2
4
Order By: Relevance
“…In particular, after stripping Asians showed the highest TEWL (Asians 1.7 times greater than Caucasians). 9,10 They concluded a resemblance with previous studies, 11,12 which concluded that skin permeability measured by TEWL, was higher in blacks than in Caucasians. They also concluded that Asian skin had the highest permeability among the study groups.…”
Section: Question 2: Do the Biophysical Properties Of Asian Skin Diffsupporting
confidence: 68%
“…In particular, after stripping Asians showed the highest TEWL (Asians 1.7 times greater than Caucasians). 9,10 They concluded a resemblance with previous studies, 11,12 which concluded that skin permeability measured by TEWL, was higher in blacks than in Caucasians. They also concluded that Asian skin had the highest permeability among the study groups.…”
Section: Question 2: Do the Biophysical Properties Of Asian Skin Diffsupporting
confidence: 68%
“…Studies generally indicate that Asians have higher stratum corneum water content [25] and higher stratum corneum lipid levels than other races [20,26,27] . Investigations involving the removal of the stratum corneum by tape stripping indicated that Asian skin may have a poor barrier function [28][29][30] . Asians compared with non-Asians have a heightened dermatological response to irritants commonly found in topical, over-the-counter, or cosmetic preparations [23,[31][32][33][34][35] .…”
Section: Differences Between Asian and Non-asian Skinmentioning
confidence: 99%
“…1 . The starting material for its synthesis, 11,11,12,12,13,13,14,14,15,15,16,16,16-tridecafluorohexadecan-1-ol, was synthesized using the methodology described previously (23). F-NA18 and its hydrocarbon analog, NA18, were synthesized from nicotinic acid and the corresponding alcohol according to literature procedures (8,16,24).…”
Section: Synthesis Of Long-chain Nicotinatesmentioning
confidence: 99%
“…Because of the protective effect against lung injury mediated by reactive oxygen species, there is growing interest in the pulmonary administration of nicotinates, especially partially fluorinated nicotinates, using a perfluorocarbon vehicle (7,8). In addition to their biological effects, nicotinates have been widely used as models to study drug uptake in vitro (9)(10)(11)(12) and in vivo (9,(13)(14)(15). Because of their potential applications, the physicochemical characteristics, such as octanol-water partition coefficients and stability toward chemical and enzymatic degradation, have been well studied (8).…”
mentioning
confidence: 99%